2010
DOI: 10.1007/s13233-010-0510-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of molecular weight of polymer matrix on the dispersion of MWNTs in HDPE/MWNT and PC/MWNT composites

Abstract: In this study, the effect of the molecular weight of the polymer matrix on the dispersion of multi-walled carbon nanotubes (MWNTs) was investigated for high-density polyethylene (HDPE)/MWNT and polycarbonate (PC)/MWNT composite materials. The dispersion of MWNTs in the polymer matrix showed a strong correlation with the melt viscosity of the polymer matrix, i.e., with the molecular weight of the polymer material. Several experimental methods, such as 4-point probe, SEM and ARES, were used to examine the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Regarding this noteworthy p c value, many parameters have been suggested to influence the percolation threshold in polymer/CNT NCs, such as the aspect ratio of the nanotubes , the degree of dispersion of the CNTs, whether they are found separately or in agglomerates , the processing method and parameters , the viscosity , molecular weight or crystallinity of the polymer matrix and the pure or functionalized nature of the nanotubes . As some of the stated parameters do not apply to the NCs of this study, the rather good dispersion observed in Figs.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Regarding this noteworthy p c value, many parameters have been suggested to influence the percolation threshold in polymer/CNT NCs, such as the aspect ratio of the nanotubes , the degree of dispersion of the CNTs, whether they are found separately or in agglomerates , the processing method and parameters , the viscosity , molecular weight or crystallinity of the polymer matrix and the pure or functionalized nature of the nanotubes . As some of the stated parameters do not apply to the NCs of this study, the rather good dispersion observed in Figs.…”
Section: Resultsmentioning
confidence: 85%
“…This t value is within the theoretical 1.6-2.0 range for three-dimensional (3D) percolating systems [45,46] (consistent with the percolation threshold on the AC conductivity versus frequency plot), indicating that a 3D percolating network was formed at 2.97 wt% MWCNTs. Regarding this noteworthy p c value, many parameters have been suggested to influence the percolation threshold in polymer/CNT NCs, such as the aspect ratio of the nanotubes [44,47], the degree of dispersion of the CNTs, whether they are found separately or in agglomerates [48], the processing method and parameters [49,50], the viscosity [18,51], molecular weight [51,52] or crystallinity [11,53] of the polymer matrix and the pure or functionalized nature of the nanotubes [39,54]. As some of the stated parameters do not apply to the NCs of this study, the rather good dispersion observed in Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Many parameters have been proposed to influence the percolation threshold in polymer/CNT NCs, such as the aspect ratio, the dispersion level and presence of agglomerates, the processing method and parameters, the nature of the matrix (viscosity, the molecular weight or crystallinity and the functionalization of the CNTs . Among those which apply to the NCs of this work, the rather good dispersion of the CNTs observed in Figure should facilitate a low percolation threshold.…”
Section: Resultsmentioning
confidence: 99%
“…[13][14][15][16][17][18] But very few studies have been reported which focus on the different interactions originated by the changes in the chemical structure of the polymer matrix itself. 19,20 The main focus of this study is to understand the effect of different numbers of methylene groups in the repeating units of various polyamides on the dispersion of multi-walled carbon nanotube (MWNT), which will influence the electrical and thermal properties, and the morphology. The samples were prepared by using the same drying procedure and the mixing was conducted at a constant mixing rate of 60 rpm.…”
Section: Introductionmentioning
confidence: 99%